Teacher Stress During the First Wave of COVID-19 Infections: An Analysis According to Demographic and Labor Variables - Vargas Rubilar, Natalia Andrea (2023)
The purpose of this study was to analyze the work situations that education professionals perceived as stressful during the first wave of COVID-19 infections, and their possible variation according to demographic characteristics and working conditions. Empirical, quantitative, ex-post-facto, cross-sectional study was carried out, in which participated 9,058 teachers (86.9% women; M age = 41.08; SD = 8.82) who completed a semi-structured questionnaire of demographic and labor information and a scale of teacher stressors in the context of a pandemic. It was used Multivariate Analysis of Variance (MANOVA) with post hoc Bonferroni contrasts to study the variations in the perception of stress according to demographic and work variables. The MANOVAs indicated significant variations in the perception of stress according to the teachers´ gender, age, marital status, having dependents (children and parents), the level of education of the teacher, the employment situation (permanent vs. transitory), teaching seniority, the type of educational management, the number of students in charge and the number of weekly working hours (for all cases, Hotelling´s F with p <.001).